Kuat Tekan dan Kuat Tarik Belah Beton Polimer Termodifikasi Alami Amylum serta Bahan Tambah Madu - Febri Satrio Nugroho; Putra Bintang Rizalditya; Rr.M.I Rretno Susilorini; Budi Santosa (G-SMART, 2017)
The resesearch used amylum as a modified polymer and honey as its added ingredient. Therewere with 3 compositions with honey, 0%; 0.03%; and 0.3%, and also 6 amylum compositions,0.1%; 0.2%; 0.5%; 1%; 2%; and 5%. The number of specimens with 20 cm in length and 10cm were 270 that were tested for compressive strength, and the number of specimens with 30cm length and 15 cm in diameter were 90 that tested for splittingtensile strength. The resultsof this research met conslusions: (1). Optimum compressive strength achieved by specimenKT-M0,03-G with 0,03% honey and 0,5% amylum of cement weight; (2) Optimum splittingtensile strength achieved by specimen KTB-M0-A with 0,% honey and 0,10% amylum of cementweight;